Evaluation of photodynamic therapy on nanoparticles and films loaded-nanoparticles based on chitosan/alginate for curcumin delivery in oral biofilms - Silvestre, Amanda Letícia Polli [UNESP]; dos Santos, Aline Martins [UNESP]; de Oliveira, Analú Barros [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2023)
Nanoparticles and nanoparticle-loaded films based on chitosan/sodium alginate with curcumin (CUR) are promising strategies to improve the efficacy of antimicrobial photodynamic therapy (aPDT) for the treatment of oral biofilms. This work aimed to develop and evaluate the nanoparticles based on chitosan and sodium alginate encapsulated with CUR dispersed in polymeric films associated with aPDT in oral biofilms. The NPs were obtained by polyelectrolytic complexation, and the films were prepared by solvent evaporation. The photodynamic effect was evaluated by counting Colony Forming Units (CFU/mL). Both systems showed adequate characterization parameters for CUR release. Nanoparticles controlled the release of CUR for a longer period than the nanoparticle-loaded films in simulated saliva media. Control and CUR-loaded nanoparticles showed a significant reduction of 3 log10 CFU/mL against S. mutans biofilms, compared to treatment without light. However, biofilms of S. mutans showed no photoinactivation effect using films loaded with nanoparticles even in the presence of light. These results demonstrate the potential of chitosan/sodium alginate nanoparticles associated with aPDT as carriers for the oral delivery of CUR, offering new possibilities to improve the treatment of dental caries and infections. This work will contribute to advances in the search for innovative delivery systems in dentistry.
Keywords: Antimicrobial photodynamic therapy; Buccal films; Chitosan; Curcumin; Polymeric nanoparticles; Sodium alginate